Adaptive control schemes for improving dynamic performance of efficiency-optimized induction motor drives. (July 2015) - Kumar, Navneet; Raj Chelliah, Thanga; Srivastava, S.P.
Abstract: Model Based Control (MBC) is one of the energy optimal controllers used in vector-controlled Induction Motor (IM) for controlling the excitation of motor in accordance with torque and speed. MBC offers energy conservation especially at part-load operation, but it creates ripples in torque and speed during load transition, leading to poor dynamic performance of the drive. This study investigates the opportunity for improving dynamic performance of a three-phase IM operating with MBC and proposes three control schemes: (i) MBC with a low pass filter (ii) torque producing current (iqs ) injection in the output of speed controller (iii) Variable Structure Speed Controller (VSSC). The pre and post operation of MBC during load transition is also analyzed. The dynamic performance of a 1-hp, three-phase squirrel-cage IM with mine-hoist load diagram is tested. Test results are provided for the conventional field-oriented (constant flux) control and MBC (adjustable excitation) with proposed schemes. The effectiveness of proposed schemes is also illustrated for parametric variations. The test results and subsequent analysis confer that the motor dynamics improves significantly with all three proposed schemes in terms of overshoot/undershoot peak amplitude of torque and DC link power in addition to energy saving during load transitions. Highlights: Field oriented control of induction motor drives (IMD) with mine-hoist load diagram with and without an energy-optimal control. Negative effects of an energy-optimal controller on the performance of IMD. Three control schemes are used to improve the dynamic performance of IMD. Energy wastage during load transition is analyzed.